Challenges on the Path to Universal Health Coverage : The Experience of Azerbaijan - Bonilla-Chacin, Maria Eugenia; Afandiyeva, Gulara; Suaya, Agustina (World Bank, Washington, DC, 2018)
The objectives of this case study are to assess how the poor fared as a result of recent efforts toward universal health coverage in Azerbaijan, and to provide an overview of the government’s planned additional reforms, in the context of a difficult economic and fiscal situation.The case study will first focus on how the poor have fared as a result of Azerbaijan’s efforts in the last decade to improve health coverage and population financial protection in case of illness. These efforts occurred during a period of strong economic performance driven by natural-resource-based economic growth. Thanks to improvements in oil and gas revenues, public expenditure on health increased six-fold since 2000. Although the organization and functioning of the system did not significantly change during this period, the additional resources were used to provide pharmaceuticals and medical supplies at no cost to the population and to refurbish the health care infrastructure. During this time, the number of drugs and medical supplies provided at no cost in inpatient care increased, while the list of outpatient care drugs and medical supplies that were provided at no cost to eligible population groups either increased or became more widely available.The positive economic and fiscal outlook the country enjoyed from the mid-2000s has significantly changed in the last two years due to a sharp decrease in oil prices. This difficult context, as well as continuous challenges in ensuring financial protection and access to services, has highlighted the need for health financing reform, as well as reform of the functioning and organization of the health system. In this context, the country recently renewed previous efforts toward implementation of a Mandatory Social Health Insurance scheme, which was mandated in 2007. To contribute to the country’s policy debates, the second objective of this case study is to discuss how this reform plan could further contribute to universal health coverage, and what challenges the country would face in its implementation.